A cost analysis of deliveries conducted in various health care settings in a city of India - Hemant Tiwari; Kinnari I Gupta; Gneyaa S Bhatt; Sheetal Vyas (Indian Association of Preventive and Social Medicine, 2011)
Background: Health is associated with various socio-economical issues which affects accessibility of a common man to the health care delivery systems. Cost analysis can be an important element in setting levels of user fees and can help sort out important economical issues. The present study was carried out to study the total cost borne in case of normal delivery and caesarean section in various health care settings and to compare them. Material & Methods: Personal interviews of 101 women delivered either by normal (ND) or by caesarean section (CS) in Government, Corporation or Private Hospital or in Home were taken. Information was collected regarding the direct medical cost, direct non medical cost and the indirect cost was analyzed by using appropriate statistical software. Results: Mean of Total cost in case of normal delivery was Rs. 575.13 (+ 172.04), Rs. 1839.73 (+ 887.07), Rs. 3035.56 (+ 1538.32), and Rs. 812.27 (+ 658.21) in Government, Corporation and Private Hospitals and in Home respectively. Mean of total cost in case of CS delivery was Rs 1823.67 (+ 801.13), Rs. 4232.87 (+ 1135.94), & Rs. 9754.67 (+ 2450.28) in respective institutions. Significant difference (p < 0.001) was found in total cost among above mentioned settings both for ND & CS. However after Post hoc analysis, no significant difference was found between total cost of normal delivery at home and at government hospital. Conclusions: The above analysis helped us to explore the cost of delivery care in above settings. As there was no significant difference found between total costs of normal delivery at home and at government hospital, people should be motivated for the Government hospital deliveries instead of home deliveries. Further research on long term outcome needs to be done.